Bone increment: A novel technique in correction of fronto-orbital deformity in patients with craniosynostosis - Ali Riazi; Bahram Aminmansoor; Ata Mahdkhah (Interdisciplinary Neurosurgery, 2023)
Background and objective: Craniosynostosis is the premature closure of one or more of the cranial sutures, which leads to skull deformities and other complications. Non-syndromic craniosynostosis (NSCS) usually involves only one cranial suture. Unicoronal (UCS) and metopic craniosynostosis (MS) are two common types of NSCS. Correction of fronto-orbital deformity is the main aim of surgical intervention in patients of UCS and MS. In this article, we express our novel technique of bone increment to use a bone graft for reshaping of the orbital rim deformity in patients diagnosed with UCS and MS. Methods: 20 patients (10 UCS and 10 MS) were treated surgically at our institute, between 2020 and 2022. The degree of the needed fronto-orbital advancement was determined preoperatively using full history, preoperative examination, three-dimensional (3D) computed tomography (CT) and longitudinal orbital projection. Results: The mean hospital stay, operative time, anesthetic duration, intraoperative blood loss and transfusion showed significantly lower results than the literature. Conclusion: The bone increment technique for fronto-orbital reshaping of patients diagnosed with UCS and MS, is an innovative and efficient reconstructive technique and may provide a valuable and alternative technique and addition in selected cases in craniofacial surgery.